Omniops gen. n. and two new species of Hydrophilini from Papua New Guinea (Coleoptera: Hydrophilidae) - Perkins, P. D.; Short, A. E.z. (Zootaxa, 2004)
Omniops gen. n. (Coleoptera: Hydrophilidae: Hydrophilini: Acidocerina) is described for two new species from Papua New Guinea: Omniops fasciatus sp. n. and O. hanseni sp. n. This genus is distinguished from other genera of Hydrophilidae by having the eyes divided into dorsal and ventral portions by an extension of the frons, and by having a row of dense long setae on the labrum. The tribal placement of the new genus and that of Quadriops Hansen are discussed. High resolution digital images are given for each holotype (online versions in color).